1979
DOI: 10.1104/pp.64.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Monoterpenes

Abstract: ABSTRACT(-)-Menthone, the major monoterpene component of the essential oil of maturing peppermint (Meathapiperita L.) laves (6 micromoles per leaf) is rapl metabolzed at the onset of flowering with a concomitant rise in the level of (-)-menthol (to about 2 micromoles per leaf). Exogenous (-)-HG3Hlmenthone is converted into (-)-I3HImenthol as the major steam-volatile product in kaf discs in flowering peppermint (10% of incorporated tracer); however, the major portion of the incorporated tracer (86%) resided in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
52
1

Year Published

1984
1984
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 13 publications
4
52
1
Order By: Relevance
“…Coincident with the overall decrease in monoterpene content of peppermint leaves is the conversion of the major monoterpene constituent, I-menthone, to i-menthol and to lesser quantities of l-menthyl acetate and d-neomenthol3 (5). Detailed examination of the metabolism of l-[G-3H]menthone in peppermint leafdiscs confirmed earlier observations that menthone was converted to menthol and menthyl acetate, and additionally revealed that up to half of the l-menthone metabolized was transformed via neomenthol to d-neomenthol-fl-D-glucoside (14,17) (Fig. 1).…”
supporting
confidence: 66%
See 3 more Smart Citations
“…Coincident with the overall decrease in monoterpene content of peppermint leaves is the conversion of the major monoterpene constituent, I-menthone, to i-menthol and to lesser quantities of l-menthyl acetate and d-neomenthol3 (5). Detailed examination of the metabolism of l-[G-3H]menthone in peppermint leafdiscs confirmed earlier observations that menthone was converted to menthol and menthyl acetate, and additionally revealed that up to half of the l-menthone metabolized was transformed via neomenthol to d-neomenthol-fl-D-glucoside (14,17) (Fig. 1).…”
supporting
confidence: 66%
“…Rapid turnover of monoterpenes has been shown to occur in mature leaves of flowering peppermint plants (Mentha piperita L.) (4,17 (14,17) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher light intensity and duration usually promote terpene accumulation (8,16), and cool nights have been found to increase monoterpene concentration in peppermint (Mentha piperita L.) before flowering (12). Monoterpene concentrations are generally higher in young leaves and peak at or before flowering (3,12), with increased rates of catabolism at the time of flowering (4,5).…”
Section: Resultsmentioning
confidence: 99%